2011
DOI: 10.1159/000327615
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide between Traditional and Nontraditional Risk Factors in Hemodialysis Patients: Analysis of Cardiovascular Mortality in a Two-Year Follow-Up

Abstract: Background: The ability of brain natriuretic peptide (BNP) together with other traditional and nontraditional risk factors to predict cardiovascular (CV) mortality in hemodialysis (HD) patients has not been well established. The aim of this prospective study was to determine the predictive cutoff values of baseline measurement of BNP along with the known CV disease risk factors to predict all-cause and CV mortality in HD patients. Methods: BNP concentration before HD was measured in 125 prevalent HD patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Twenty-seven relevant studies reporting on 8,666 individuals were identified from 16 countries. Thirteen studies were based in Europe [4] , [7] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , 5 in North America [5] , [26] , [27] , [28] , [29] , [30] , 2 in Australia [31] , [32] and and 6 in East Asia [6] , [33] , [34] , [35] , [36] , [37] . From all primary studies, over 63.4% of patients were receiving hemodialysis (HD).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven relevant studies reporting on 8,666 individuals were identified from 16 countries. Thirteen studies were based in Europe [4] , [7] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , 5 in North America [5] , [26] , [27] , [28] , [29] , [30] , 2 in Australia [31] , [32] and and 6 in East Asia [6] , [33] , [34] , [35] , [36] , [37] . From all primary studies, over 63.4% of patients were receiving hemodialysis (HD).…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the patients of the study had any sign of heart failure. Additionally, BNP measures in dialysis patients with echocardiographically diagnosed heart failure were more than 5 times higher than in our population [42] and BNP levels in our population are within a range that was identified as beneficial in a prospective 2-year mortality analysis [43]. …”
Section: Discussionmentioning
confidence: 92%
“…In a 5-year cohort study of more than 88,000 MHD patients in the United States conducted by Jessica E Miller et al, it had been reported that the greatest survival gain of higher HD dose was associated with a Kt/V approaching the 1.6 to 1.8 range 16 . In contrast, several studies had shown that increasing dialysis dose has no effect on survival gain and no predictive effect on cardiovascular death 17 – 19 . The hemodialysis (HEMO) study compared the outcomes of patients at high dialysis doses (target spKt/V approximately 1.65) with those at standard dialysis doses (target spKt/V approximately 1.25) and showed no significant differences in all-cause and cardiovascular deaths 20 .…”
Section: Introductionmentioning
confidence: 98%